Results and Relevance of Molecular Detection of Pathogens by SeptiFast – A Retrospective Analysis in 75 Critically Ill Children - Tschiedel, E.; Steinmann, J.; Buer, J.; Onnebrink, J. G.; Felderhoff-Müser, U.; Rath, P.-M.; Dohna-Schwake, C. (Klinische Pädiatrie, 2012)
Sepsis is a common cause of death in children. Early detection of bloodstream pathogens is crucial for the appropriate antibiotic treatment. Blood cultures (BC) are the gold standard test used for detection. Recently, additional molecular detection methods of microbial DNA by multiplex PCR (SeptiFast, SF) have become available.Our retrospective study was aimed to compare results of BC to those of SF regarding results and therapeutic relevance.We identified a total of 110 SF samples in 75 patients with suspected systemic infection by retrospective chart review. Each patient underwent SF and BC testing simultaneously.The initial analysis displayed no statistical significant difference in positive SF results compared to BC (p=0.19): in 26 of 110 samples (24%) microbial DNA was found. 19 BC (17%) showed microbial growth. 14 samples were positive in SF but negative in BC (13%). In patients who were pretreated with antibiotics (n=97) pathogens were identified in 24 samples by SF (25%) but only in 11 samples by BC (11%). Based on the clinical presentation and the spectrum of bacterial isolates 3 BC were considered contaminated. Considering this, SF yielded pathogens significantly more often than BC in the overall study population (p=0.04). SF results were available at least 31 h before BC results. Based on SF result antibiotic therapy was adjusted in 14 patients (13%).Molecular detection of pathogens by SF was faster and more frequently positive than BC. We have therefore demonstrated that SF might be superior to BC in testing for bloodstream pathogens. Prospective multicentric studies are required to determine whether this hypothesis can be maintained.
Keywords: SeptiFast; blood culture; pediatric; antibiotic therapy